2020
DOI: 10.1155/2020/7826519
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome and Predictors of Intestinal Obstruction Surgery in Ethiopia: A Cross-Sectional Study

Abstract: Background. Despite the advancement in the healthcare system, the impact of surgical interventions on public health systems will continue to grow. But predicting the outcome is challenging. Concerns related to unexpected outcomes and delays in the diagnosis of postoperative complications are the major issue. Intestinal obstruction is a common life-threatening surgical condition followed by fatal and nonfatal postoperative complications. This study was aimed at assessing results after surgery for intestinal obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
3
10
1
Order By: Relevance
“…This study found that − 116 (59.2%) of patients managed for bowel obstruction had favorable management outcome. Although this result is comparable to the result of the study in Turkey (58.1%) [20], it is lower than the ndings of the study done in Nekemte specialized hospital-73.5% [10], Adama Hospital-75.4% [11], Asella hospital-75.7% [12], Adama Hospital-75.4% [11], Arba Minch General Hospital-77.7% [13], Chiro Hospital-78.7% [14], Dilla Hospital-86.4% [15], University of Gondar Comprehensive Specialized Hospital-83.3% [16], Debre Birhan Referral Hospital-83.3% [4], 82% in south Wollo Zone hospitals [17], 77% in Wolayita [18], Kenya-86.4% [26], and India-74% [27]. The possible reason for the observed discrepancy might be the difference in the way the management outcome was operationalized and measured, the difference in the professionals involved in the surgical management, the difference in the study settings, study period, and population.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…This study found that − 116 (59.2%) of patients managed for bowel obstruction had favorable management outcome. Although this result is comparable to the result of the study in Turkey (58.1%) [20], it is lower than the ndings of the study done in Nekemte specialized hospital-73.5% [10], Adama Hospital-75.4% [11], Asella hospital-75.7% [12], Adama Hospital-75.4% [11], Arba Minch General Hospital-77.7% [13], Chiro Hospital-78.7% [14], Dilla Hospital-86.4% [15], University of Gondar Comprehensive Specialized Hospital-83.3% [16], Debre Birhan Referral Hospital-83.3% [4], 82% in south Wollo Zone hospitals [17], 77% in Wolayita [18], Kenya-86.4% [26], and India-74% [27]. The possible reason for the observed discrepancy might be the difference in the way the management outcome was operationalized and measured, the difference in the professionals involved in the surgical management, the difference in the study settings, study period, and population.…”
Section: Discussioncontrasting
confidence: 44%
“…In our study, favorable management outcome was affected by gangrenous intraoperative nding. This is supported by the study conducted in Wolayita [18], Asella hospital [12], Arba Minch General Hospital [13], Chiro, Dilla, and Adama hospitals in which patients with viable small bowel volvulus and viable sigmoid volvulus were more likely to have favorable surgical management outcome compared to their counterparts [11,14,15].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…as intra operative ndings of gangrenous small and large bowels, length of hospital stay, duration of illness before treatment, comorbidity, Hemoglobin, WBC, post & pre-operative complications and age was independent predicator of mortality for adult patients treated surgically.The odds of gangrenous large bowel obstructions to cause mortality after treated bowel obstruction surgically was 5.5 times higher than viable large bowel (AOR 5.58; 95%CI [2.33, 3.36), p=0.0001]. The odds old age (>=55) to cause mortality after treatment of bowel obstruction surgically was 3.7 times higher than compared with age groups(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) years old ((…”
mentioning
confidence: 95%
“…Intestinal obstruction is one of the most common reasons of all emergency department visits for acute abdominal pain ( 1 ). Serious complications such as septic shock, intestinal perforation, severe electrolyte disturbance, and multiple organ dysfunction syndrome may occur, which may lead to approximately 5%–10% death rate ( 14 ). The treatment strategies for acute intestinal obstruction are relatively complex, which could be mainly divided into surgery treatment and conservative treatment ( 3 , 15 ).…”
Section: Discussionmentioning
confidence: 99%